PENGARUH ETIKA BIROKRASI TERHADAP KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KETAPANG - Mega Herdiyanti E.42008021 (GOVERNANCE, Jurnal Ilmu Pemerintahan, 2012)
This essay intended to prove theories from experts that related with influence ethics of bureaucracy againtsservice quality of population administration that implemented at Dinas Kependudukan dan Pencatatan Sipil ofKetapang district. The title of essay be appointed from service quality issues that occured in the office especiallyrelating with ethicsof bureaucracy indicated in the service. This researh used quantitative research withdescriptive methods. The location of research is Dinas Kependudukan dan Pencatatan Sipil of Ketapang district.Subject of this research is peoples who receive services in this office as many as 77 peoples. The summary ofthis research is there influence ethics of bureaucracy to service quality of population administration in this officein the amount of 46,38 % and 53,62% influenced by others factor, that are discretionary authority, attitude thatoriented of change, organizational culture, ethics of bureaucracy, intensive system, spirit of hard work, politicculture, dinamics and developments of political, local conflict management, socio-economic conditions, andcontrols was perfomed by community and organization NGO.Keyword: Ethics of bureaucracy, service, service quality